Using Happiness Surveys to Value Intangibles: The Case of Airport Noise - Bernard M.S. van Praag; Barbara E. Baarsma (Center for Economic Studies and ifo Institute (CESifo), 2004)
Inhabitants of houses near Amsterdam Airport are complaining of noise nuisance, caused by aircraft traffic. The usual assumption is that the effect of the externality will be perfectly reflected by house price differentials. This is based on the implicit assumption that there is a well-functioning housing market. If that is not true, we need a correction method in order to assess the intangible damage. We assess the monetary value of the noise damage, caused by aircraft noise nuisance around Amsterdam Airport as the sum of hedonic price differentials and a residual cost component. The residual costs are assessed from a survey, including an ordinal life satisfaction scale, on which individual respondents have scored. The derived compensation scheme depends on, among other things, the objective noise level, income, the degree to which prices account for noise differences, and the presence of noise insulation.
Keywords: 330; cost-benefit analysis; externalities; airport noise; satisfaction analysis; residual shadow costs